(3CSFdI aj GdQLGds - (3GdSgej GdbQTj GdLQLGfj, CHh GdbGSe, MeRI Hf jhSa Hf EHQGgje, J (B427 (3g`s
(3ChdgG (B:s
(3PcQ CHh GdbGSe MeRI Hf jhSa GdTgQj aj SDGdGJg ; SFd GdOejGWj Yf eMeO Hf ZGdH JeGe abGd KbI eCehf EdG Gfg cGf jNWjA hcGf hge aj CMGOjK efgG Cfg MOK Yf (B...s
(3BNQgG (B:s
... (3HMOjK TYHI Yf GdMce Yf ebSe Yf GHf YHGS dG jMQe HGdML EdG aj CTgQ GdML bGd CHh GdMSf MOK YHO Gddg HgPG eYGP Gddg eG MOK GdYeQj HgPG GdTQcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\280s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdMOjK hGdeUWdMs